Adverse childhood experiences and COVID-19 vaccination uptake: Examining the intersection of sex and urban-rural residence - Karyn Fu; Dylan B. Jackson; Alexander Testa (PLoS ONE, 2025)
Background Adverse childhood experiences (ACEs) have been linked to negative health outcomes and behaviors in adulthood. Despite widespread research on ACEs, their relationship with COVID-19 vaccination uptake, particularly heterogeneity across demographic groups, remains underexplored. This study examined the association between ACEs and COVID-19 vaccination status, with a focus on how this relationship varies by sex and urban-rural residence. Methods Data were obtained from the 2022 Behavioral Risk Factor Surveillance System (BRFSS), including respondents who participated in the ACEs and COVID-19 vaccination optional state modules (N = 12,085 adults). COVID-19 vaccination status (yes/no) served as the dependent variable, while ACEs were categorized into four levels: 0, 1, 2–3, and 4 + ACEs. Multivariable logistic regression analyses, stratified by sex and urban-rural residence, were conducted to assess the association between ACEs and vaccination status. Results Among the sample, 76.2% reported receiving at least one dose of the COVID-19 vaccine. Multivariable analysis revealed no statistically significant association between ACEs and vaccination status for the full sample. Stratified analyses indicated that male respondents living in rural counties with 4 + ACEs had significantly lower odds of vaccination (adjusted odds ratio [aOR] = 0.57, 95% CI = 0.34–0.96). No significant associations were observed for other demographic groups (e.g., females in urban or rural areas; males in urban areas). Conclusions The findings suggest that males in rural areas with high ACE exposure may be vulnerable to low COVID-19 vaccination uptake. Targeted trauma-informed public health interventions warrant consideration to address vaccination uptake among this population.